Analisis Penerapan Metode Penyusutan Aset Tetap Pada Pabrik Tahu Tempe Waidoko Kel. Wolomarang - Maria Dhapa; Henrikus Herdi; Wihelmina Maryetha Yulia Jaeng (Universitas Maritim AMNI Semarang, 2023)
This study aims to know and analyze the depreciation method of fixed assets applied to the Tempe Waidoko Tofu Factory, Wolomarang Village. Research data is obtained from (secondary) data obtained from documentance and direct interviews with related parties. The analytical method used in this study is quantitative descriptive analysis, which is an analysis that describes the depreciation method of fixed assets applied by the Tempe Waidoko tofu factory Kelurahan Wolomarang using H straight-line depreciation method and double declining balance method. The results showed that the fixed asset depreciation method used in the tempeh tofu factory was a straight-line method. Because the straight-line method is greater in book value than the double declining balance method.